Let Me Out of Here: A Story of Using Comics to Heal During the Pandemic - Sydney Phillips Heifler (The Comics Grid: Journal of Comics Scholarship, 2022)
This graphic essay details the hardships I faced during the pandemic. It highlights the importance of comic-making to combat present-day isolation and hardship and aid recovery from trauma. During the first year of my Ph.D. I experienced a miscarriage, my step-grandfather passed away with Covid, and, at the start of my second semester, I was sexually assaulted, resulting in a physical injury that has yet to heal. The emotional and physical trauma of these incidents put me behind in my coursework. To cope, I engaged in art therapy and completed a trauma recovery program. Often, my recovery has been aided by and expressed through the digital comics I create, which are generally poetry comics. By expressing the weight of these traumatic incidents in drawings and text, I acknowledged their significance and found some relief and self-consolation. In sharing my experience, I hope to impart the importance of comics in this moment by showing how creating them helped me process trauma created and exacerbated by the pandemic.